Prevention of oral mucositis in patients with breast cancer in neoadjuvant chemotherapy: Case reports (Research, Society and Development, 2025)
This article aimed to report the routine dental follow -up, to prevent oral mucositis of two patients under neoadjuvant chemotherapy for the control of breast cancer assisted in a Oncology Center of the Unified Health System (SUS), Recife, Northeast, Brazil. After complying with the inclusion criteria, participants signed the free and informed consent form, underwent initial dental evaluation and were oriented regarding the oral care to be instituted during chemotherapy. In addition, the preventive follow -up of mucositis with low level laser therapy was suggested. In both reported cases, there was only a brief account of oral mucositis episode. However, due to difficulties related to locomotion and indisposition related to the systemic effects of chemotherapy, laser therapy can only be implemented in one of the patients, with a lower than the proposal. It can be observed the importance of personalized cancer dental care in order to favor the self-care and provide quality of life during the chemotherapy.